Clinical impact of influenza vaccination after ST- and non-ST-segment elevation myocardial infarction - insights from the IAMI trial - Fröbert, Ole; Götberg, Matthias; Erlinge, David; Akhtar, Zubair; Christiansen, Evald H; MacIntyre, Chandini R; Oldroyd, Keith G; Motovska, Zuzana; Erglis, Andrejs; Moer, Rasmus; Hlinomaz, Ota; Jakobsen, Lars; et al. (The American heart journal, 2023)
BACKGROUND: Influenza vaccination early after myocardial infarction (MI) improves prognosis but vaccine effectiveness may differ dependent on type of MI. METHODS: A total of 2,571 participants were prospectively enrolled in the Influenza vaccination after myocardial infarction (IAMI) trial and randomly assigned to receive in-hospital inactivated influenza vaccine or saline placebo. The trial was conducted at 30 centers in eight countries from October 1, 2016 to March 1, 2020. Here we report vaccine effectiveness in the 2,467 participants with ST-segment elevation MI (STEMI, n = 1,348) or non-ST-segment elevation MI (NSTEMI, n = 1,119). The primary endpoint was the composite of all-cause death, MI, or stent thrombosis at 12 months. Cumulative incidence of the primary and key secondary endpoints by randomized treatment and NSTEMI/STEMI was estimated using the Kaplan-Meier method. Treatment effects were evaluated with formal interaction testing to assess for effect modification. RESULTS: Baseline risk was higher in participants with NSTEMI. In the NSTEMI group the primary endpoint occurred in 6.5% of participants assigned to influenza vaccine and 10.5% assigned to placebo (hazard ratio [HR], 0.60; 95% CI, 0.39-0.91), compared to 4.1% assigned to influenza vaccine and 4.5% assigned to placebo in the STEMI group (HR, 0.90; 95% CI, 0.54-1.50, P = .237 for interaction). Similar findings were seen for the key secondary endpoints of all-cause death and cardiovascular death. The Kaplan-Meier risk difference in all-cause death at one year was more pronounced in participants with NSTEMI (NSTEMI: HR, 0.47; 95% CI 0.28-0.80, STEMI: HR, 0.86; 95% CI, 0.43-1.70, interaction P = .028). CONCLUSIONS: The beneficial effect of influenza vaccination on adverse cardiovascular events may be enhanced in patients with NSTEMI compared to those with STEMI.
Keywords: výsledek terapie; infarkt myokardu; vakcíny proti chřipce; rizikové faktory; Influenza, Human; Treatment Outcome; Influenza Vaccines; lidé; infarkt myokardu s elevacemi ST úseků; Non-ST Elevated Myocardial Infarction; infarkt myokardu bez ST elevací; ST Elevation Myocardial Infarction; Risk Factors; Humans; chřipka lidská; Myocardial Infarction